Chemometrics-assisted excitation-emission fluorescence spectroscopy on nylon-attached rotating disks. Simultaneous determination of polycyclic aromatic hydrocarbons in the presence of interferences - Cañas, Alejandro (2014)
This work presents a green and very simple approach which enables the accurate and simultaneous determination of benzo[a]pyrene, dibenz[a,h]anthracene, benz[a]anthracene, and chrysene, concerned and potentially carcinogenic heavy-polycyclic aromatic hydrocarbons (PAHs) in interfering samples. The compounds are extracted from water samples onto a device composed of a small rotating Teflon disk, with a nylon membrane attached to one of its surfaces. After extraction, the nylon membrane containing the concentrated analytes is separated from the Teflon disk, and fluorescence excitation–emission matrices are directly measured on the nylon surface, and processed by applying parallel factor analysis (PARAFAC), without the necessity of a desorption step. Under optimum conditions and for a sample volume of 25 mL, the PAHs extraction was carried out in 20 min. Detection limits based on the IUPAC recommended criterion and relative errors of prediction were in the ranges 20–100 ng L−1 and 5–7%, respectively. Thanks to the combination of the ability of nylon to strongly retain PAHs, the easy rotating disk extraction approach, and the selectivity of second-order calibration, which greatly simplifies sample treatment avoiding the use of toxic solvents, the developed method follows most green analytical chemistry principles.